BANTUAN LUAR NEGERI AUSTRALIA KEPADA NAURU MELALUI PACIFIC SOLUTION TAHUN 2001-2007 - Natasha Hidayah Arifin; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study analyzes foreign aid provided by Australia through Pacific Solution. The number of refugees and Asylum Seeker who come to Australian territory every year has a big impact on Australia. So to curb the flow of refugees, and save Australia from the threat of refugees and illegal , Asylum Seeker, the Australian state issued a policy in the form of Pacific Solution. With this policy , Asylum Seeker and refugees are transferred to detention centers spread across island countries in the Pacific Ocean, one of the country is Nauru. One of the policy application strategies is Operation Relex, which is a strategy to protect Australia's territorial borders on the high seas by intercepting, detaining and preventing ships carrying people who want to enter Australia without a visa. This research applied qualitative method with data collection technique through literature study sources from books, journal, article and website that related to foreign aid and pacific solution. This research show that the provision of foreign aid through the Pacific Solution policy has succeeded in restraining the flow of refugees and Asylum Seeker who come to Australian territory. To maintain Australian sovereignty from the threat of refugees and Asylum Seeker. Australia must continue to provide foreign assistance to Nauru, so that Nauru remains willing to become a shelter for refugees and , Asylum Seeker. Keywords: Foreign Aids, Pacific Solution, Refugee, Asylum Seeker, Detention Center, Operation Relex